Brochoscopy Intervention using Laryngeal Mask Airway in Infant for Severe Airway Stenosis - Qinghao Cheng; Lei Li (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Fibreoptic bronchoscopy (FB) and laryngeal mask airway (LMA) have been used successfully in children since the early 1980s [1,2]. The paediatric fibreoptic bronchoscopy visa laryngeal mask airway (LMA) in general anesthesia was established in 1990s [3,4]. Although previous studies have shown some experience on FB in infant, conclusive effects on bronchoscopy intervention are unknown. We report the use of laryngeal mask airway (LMA) to guide electric bronchoscopy interventions (EBI) while maintaining an adequate depth of anesthesia and effective ventilation in small infant who was diagnosed of having severe airway stenosis from computed tomography (CT) scan.